Alex Delaware : Rage - Book 19 - Kellerman, Jonathan (New York : Random House Large Print, 2005)
Troy Turner and Rand Duchay were barely teenagers when they kidnapped and murdered a younger child. Troy, a remorseless sociopath, died violently behind bars. But the hulking, slow-witted Rand managed to survive his stretch. Now, at age twenty-one, hes emerged a haunted, rootless young man with a pressing need to talk once again with psychologist Alex Delaware. But the young killer comes to a brutal end, that conversation never takes place. Or has someone waited for eight patient years to dine on ice-cold revenge? Both seem strong possibilities to Sturgis, but Delawares suspicions run deeper and darker. Because fear in the voice of the grownup Rand Duchay, and his eerie final words to Alex "Im not a bad person" betray untold secrets. Buried revelations so horrendous, and so damning, theyre worth killing for. As Delaware and Sturgis retrace their steps through a grisly murder case that devastated a community, they discover a chilling legacy of madness, suicide, and multiple killings left in its wake, and even uglier truths waiting to be unearthed. And the nearer they come to understanding an unspeakable crime, the more harrowingly close they get to unmasking a monster hiding in plain sight.
Keywords: Delaware, Alex -- (Fictitious character); Fiction; Sturgis, Milo -- (Fictitious character); Fiction; Police -- California; Los Angeles; Fiction; Juvenile justice, Administration of; Fiction; Boys; Crimes against; Fiction; Psychologists -- Fiction; Los Angeles (Calif.) -- Fiction; Psychological fiction; Detective and mystery fiction